Preparation method of thermal interface composite material with high toughness and high heat conductivity coefficient
Through the combination of sea urchin-shaped metal thermal filler and silicone resin, the problem of insufficient thermal conductivity and mechanical properties of thermal composite materials is solved, and a thermal interface composite material with high thermal conductivity coefficient and high mechanical flexibility is realized, which simplifies the preparation process and reduces the Energy consumption.
Patent Information
- Application Number
- CN202411193566.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-28
AI Technical Summary
The existing thermally conductive composite materials are difficult to balance the improvement of thermal conductivity and mechanical flexibility. The preparation process is complex and the conditions are harsh, resulting in insufficient thermal conductivity and mechanical properties of thermal interface composite materials.
Nanoparticles are prepared by electrodeposition and combined with materials such as silicone resin to form a thermal interface composite material with a high specific surface area to improve thermal conductivity and mechanical flexibility.
It achieves thermal conductivity up to 8.0W/mK and excellent mechanical flexibility, while simplifying the preparation process, reducing energy consumption and process complexity, and has the prospect of industrial application.
Smart Images

Figure CN119119734A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of thermally conductive composite materials, and in particular relates to a method for preparing a high-toughness and high-thermal conductivity thermal interface composite material. Background Art
[0002] With the rapid development of electronic information technology such as wireless base stations and 5G communication equipment, electronic devices are becoming increasingly high-power and integrated, causing a sudden increase in the heat density in the system, seriously threatening the stability of the device. Thermally conductive polymer composite materials have many advantages such as good thermal conductivity, high specific strength, and easy molding and processing, and have become key materials in the field of interface thermal conductivity.
[0003] The intrinsic thermal conductivity of polymers is poor, and the most effective way to improve thermal conductivity is to introduce high thermal conductivity fillers to construct thermal conductive composite materials and design continuous thermal conductive paths. The thermal conductive fillers are closely arranged to construct anisotropic continuous thermal conductive paths through template method, freeze drying method, mechanical stretching method and magnetic field induction, which can significantly improve thermal conductivity. However, its preparation process is complicated and the conditions are harsh, which makes it difficult to meet the requirements of practical applications.
[0004] On the other hand, the continuous thermal network of one-dimensional linear and tubular thermal conductive fillers in the composite system exhibits high thermal conductivity, but the one-dimensional fillers with high aspect ratio are easy to entangle, which makes the viscosity of the prepolymer liquid increase sharply, resulting in a decrease in interface wettability and a sudden increase in interface thermal resistance; zero-dimensional spherical filling thermal conductive composite materials have the advantages of low prepolymer viscosity, small interface thermal resistance, simple preparation and convenient operation, but the effective contact surface of the spherical structure is small, it is difficult to form a continuous thermal conductive path, and the thermal conductivity is difficult to further improve. Therefore, the preparation of thermal interface composite materials that take into account both high thermal conductivity and high mechanical flexibility has always been a research difficulty in the field of thermal interface composite materials. Summary of the invention
[0005] In order to solve the problem of insufficient thermal conductivity and mechanical flexibility of existing thermally conductive composite materials, the present invention utilizes metal thermally conductive fillers with sea urchin-like fractal growth and the physical integration of the sea urchin-like morphology of the thermally conductive filler, which not only improves the thermal conductivity of the composite material, but also improves the mechanical flexibility of the composite material at the same time.
[0006] One of the purposes of the present invention is to provide a high-toughness and high-thermal conductivity thermal interface composite material. The high-toughness and high-thermal conductivity thermal interface composite material provided by the present invention has the characteristics of high thermal conductivity, high toughness and high tensile strength.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned high-toughness and high-thermal conductivity thermal interface composite material.
[0008] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a high-toughness and high-thermal conductivity thermal interface composite material, which includes a matrix resin and a metal thermal conductive filler; further, the thermal conductivity of the thermal interface composite material is greater than 8.0W / mK, and maintains high mechanical flexibility within a wide temperature range.
[0009] Furthermore, the matrix resin includes silicone resin, a curing agent, a catalyst and a functional additive, and the thermal conductive filler is fractally grown metal nanoparticles.
[0010] Furthermore, the organic silicone resin includes one or a combination of at least two of linear vinyl silicone resin, branched vinyl silicone resin, modified silicone resin or silicone gel.
[0011] Furthermore, the curing agent is one or a combination of at least two of hydroxy silicone oil, vinyl silicone oil, hydrogen-containing silicone oil or phenyl silicone oil.
[0012] Furthermore, the catalyst is at least one of a complex of chloroplatinic acid and isopropyl alcohol or divinyltetramethylsiloxane or diethyl phthalate.
[0013] Furthermore, the functional additive is one or a combination of at least two of a thickener, an anti-aging agent, an anti-corrosion agent, and a flame retardant.
[0014] Furthermore, the metal thermal conductive filler is at least one of gold, silver, copper, aluminum, iron, zinc, and nickel nanoparticles.
[0015] Furthermore, the fractal growth morphology of the metal thermal conductive filler is spherical and sea urchin-shaped.
[0016] Furthermore, the mass ratio of the silicone resin to the thermally conductive filler is 5-20:1, the mass fraction of the curing agent in the matrix resin is 1%-5%, the mass fraction of the catalyst in the matrix resin is 0.05%-2%, and the mass fraction of the functional additive in the matrix resin is 0.1%-5%.
[0017] A method for preparing a high-toughness and high-thermal conductivity thermal interface composite material, the specific steps are: (1) Preparation of fractal growth metal thermal conductive fillers 1) preparing the electrolyte: metal nitrate as the electrodeposition metal salt, ionic liquids of formula (Ⅰ-Ⅰ) and (Ⅰ-Ⅱ) as additives, and dimethyl sulfoxide as the solvent;
[0018] Furthermore, the synthesis of the ionic liquid additives of formula (I-I) and (I-II) structures comprises the following specific steps: Add a solution A of chloromethyl ether in acetonitrile to a solution B of the intermediate product of formula II or III, react at 60-90° C. for 12-24 hours, and then post-treat to obtain an ionic liquid additive of formula (I-I) or (I-II); the ratio of the amount of the intermediate product of formula II or III to the amount of chloromethyl ether is 1:1.0-5.0;
[0019] Furthermore, in the synthesis steps of the ionic liquid additives of formula (I-I) and (I-II), the volume of acetonitrile in the solution A is recorded as 10-20 mL / g based on the mass of the intermediate product shown in formula II or III; Furthermore, in the synthesis steps of the ionic liquid additives of formula (I-I) and (I-II), the volume of acetonitrile in the solution B is recorded as 1-5 mL / g based on the mass of chloromethyl ether; Furthermore, in the synthesis step of the ionic liquid additives of the structures of formula (Ⅰ-Ⅰ) and (Ⅰ-Ⅱ), the post-treatment method is: the reaction solution is evaporated under reduced pressure to remove the solvent acetonitrile, the remaining mixture is fully washed three times with ether, the solvent is evaporated under reduced pressure and fully dried to obtain the ionic liquid additive of the structure shown in formula (Ⅰ-Ⅰ) or (Ⅰ-Ⅱ).
[0020] 2) Electrodeposition: Using ITO conductive glass as cathode and anode, respectively, electro-deposit the electrolyte prepared in step 1) containing ionic liquid additives of formula (Ⅰ-Ⅰ) and (Ⅰ-Ⅱ) in an electrolytic cell to obtain spherical and sea urchin-shaped metal nanoparticles, respectively, which are washed and dispersed in tetrahydrofuran solution for later use.
[0021] Furthermore, in the electrodeposition step, the ITO conductive glass has a length of 5 to 50 cm, a width of 3 to 20 cm, a thickness of 0.5 to 5 mm, and a sheet resistance of 1 to 100 Ω / cm 2 .
[0022] Furthermore, the distance between the cathode and the anode is 0.02-1.0 cm.
[0023] Furthermore, the concentration of the ionic liquid additive in the electrolyte is 10-200 mg / mL, the concentration of the metal nitrate is 50-150 mg / mL, and the total amount of the electrolyte is 50-300 mL.
[0024] Furthermore, the electrodeposition voltage is 5-20 V, and the current density is 10-100 mA / cm 2 .
[0025] The invention discloses a nano-metal particle thermal conductive filler having a fractal growth shape of a sphere or a sea urchin by electro-depositing an electrolyte containing an ionic liquid additive having a structure shown in formula (I-I) or (I-II).
[0026] (2) Preparation of high-toughness and high-thermal conductivity thermal interface composite materials The silicone resin, curing agent and catalyst are mixed and stirred for 10 to 60 minutes to obtain a resin precursor, and then spherical or sea urchin-shaped metal nanoparticle thermal conductive filler is added and stirred for 10 to 60 minutes, and then it is applied into a 1 to 15 mm thick film, and cured at 50 to 140° C. for 5 to 60 minutes to obtain the high-toughness and high-thermal conductivity thermal interface composite material.
[0027] Furthermore, the stirring speed is 100-800 rpm.
[0028] The thermal interface composite material prepared by the present invention has a thermal conductivity greater than 8.0 W / mK and maintains high mechanical flexibility within a wide temperature range.
[0029] Compared with the prior art, the present invention has the following advantages: The present invention adopts a metal thermal conductive filler with a fractal growth morphology in the shape of a sea urchin. Based on the high specific surface area and physical interlocking effect of the sea urchin-shaped filler, the provided thermal interface composite material is easy to prepare and has a thermal conductivity of up to 8.0 W / mK and excellent mechanical flexibility. It also has the characteristics of low energy consumption, simple process, safety and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 : A schematic diagram of the structure of the electrodeposition device in Example 3 of the present invention; Figure 2 : The morphology of the electrodeposited silver metal particles in Example 4 of the present invention; Figure 3 : The morphology of the electrodeposited silver metal particles in Example 5 of the present invention; DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, but the protection scope of the present invention is not limited thereto.
[0032] The present invention utilizes the basic principle of physical interlocking of sea urchin-shaped metal thermal conductive fillers to increase the contact area between fillers, effectively reduce the load of fillers, and achieve thermal conductivity enhancement and mechanical toughening performance of thermal interface composite materials. The thermal conductivity of the thermal interface composite material of the present invention is greater than 8.0 W / mK, and maintains high mechanical flexibility over a wide temperature range. The high-toughness and high-thermal conductivity thermal interface composite material prepared by the method of the present invention has good processing fluidity, is easy to control production operations, and has broad industrialization and market prospects.
[0033] Example 1 Synthesis of 1,1-dimethyl ethyl ether morpholine chloride At 25°C, morpholine (20.0 mmol) and KOH (20.0 mmol) were stirred in CH3CN (20.0 mL) for 3 h, and then 1-chloromethyl ether (20.0 mmol) was added to the mixture and the reaction was continued under reflux for 48 h. The reaction mixture was subjected to rotary evaporation to remove the volatile solvent CH3CN, CH2Cl2 was added to the residue, extracted three times with water, and the organic phase was thoroughly dried with anhydrous Na2SO4. The collected organic phase filtrate was subjected to rotary evaporation to remove the solvent, and then thoroughly washed with ether three times. The solid product obtained by removing the ether was finally dried in a dynamic vacuum oven at 45°C for 24 h to obtain the intermediate product shown in formula (II). At 25°C, the intermediate product shown in formula (II) (20.0 mmol) and 1-chloromethyl ether (20.0 mmol) were continued to react in CH3CN (20.0 mL) under reflux for 48 h. The reaction mixture was subjected to rotary evaporation to remove the volatile solvent CH3CN, and then washed thoroughly three times with ether. The solid product obtained by removing the ether was finally dried in a dynamic vacuum oven at 45°C for 24 h to obtain a solid product represented by formula (Ⅰ-Ⅰ) with a yield of 76.9%.
[0034]
[0035] Example 2 Synthesis of 1,1-dimethyl ether pyrrole chloride At 25°C, pyrrolidine (20.0 mmol) and KOH (20.0 mmol) were stirred in CH3CN (20.0 mL) for 3 h, and then 1-chloromethyl ether (20.0 mmol) was added to the mixture and the reaction was continued under reflux for 48 h. The reaction mixture was subjected to rotary evaporation to remove the volatile solvent CH3CN, CH2Cl2 was added to the residue, extracted three times with water, and the organic phase was thoroughly dried with anhydrous Na2SO4. The collected organic phase filtrate was subjected to rotary evaporation to remove the solvent, and then thoroughly washed three times with ether. The solid product obtained by removing the ether was finally dried in a dynamic vacuum oven at 45°C for 24 h to obtain the intermediate product shown in formula (III). At 25°C, the intermediate product shown in formula (III) (20.0 mmol) and 1-chloromethyl ether (20.0 mmol) were continued to react in CH3CN (20.0 mL) under reflux for 48 h. The reaction mixture was subjected to rotary evaporation to remove the volatile solvent CH3CN, and then washed thoroughly three times with ether. The solid product obtained by removing the ether was finally dried in a dynamic vacuum oven at 45°C for 24 h to obtain a solid product represented by formula (Ⅰ-Ⅱ) with a yield of 73.1%.
[0036]
[0037] Example 3 like Figure 1 The present embodiment provides an electrodeposition device for precisely controlling the morphology of electrodeposited nano-metal particles, which includes two conductive electrodes 1 and 2 arranged in parallel and correspondingly in an electrolytic cell 3, and an electrolyte 4 formed between the two conductive electrodes. The specific manufacturing process is as follows: placing the electrolyte 4 containing an ionic liquid additive, a metal salt and a solvent in the electrolytic cell, placing the conductive surfaces of the two conductive electrodes (indium tin oxide glass) 1 and 2 in parallel relative to each other, respectively serving as an anode and a cathode; Example 4 (1) Preparation of spherical metal thermal conductive fillers 10-50 parts of the ionic liquid additive having the structure shown in formula (I-I) are dissolved in a solution of 20-50 parts of dimethyl sulfoxide containing 2-10 parts of copper nitrate, and the mixture is stirred thoroughly. The electrodeposition electrolyte formed above is placed in an electrolytic cell, two conductive electrodes with a thickness of 1 mm are taken, the distance between them is set to 0.5 cm, a bias voltage of 5 V is applied, and spherical nanoparticles of metallic copper are obtained at the cathode.
[0038] (2) Preparation of spherical metal thermal conductive filler-thermal interface composite materials The organic silicon resin, curing agent and catalyst were mixed in a mass ratio of 98:1:1, and stirred at a speed of 500 rpm for 30 minutes to obtain a resin precursor. Then, the spherical metal nanoparticle thermal conductive filler prepared above was added, wherein the mass ratio of the thermal conductive filler to the organic silicon resin was 1:5, and stirred at a speed of 500 rpm for 30 minutes, and then applied into a 5.0 mm thick film, and cured at 100° C. for 20 minutes to obtain the thermal interface composite material filled with the spherical metal thermal conductive filler, such as Figure 2 shown.
[0039] Example 5 (1) Preparation of fractal growth sea urchin-shaped metal thermal conductive filler 10-50 parts of the ionic liquid additive of the structure shown in formula (I-II) are dissolved in a solution of 20-50 parts of dimethyl sulfoxide in 2-10 parts of copper nitrate, and the mixture is stirred thoroughly. The electrodeposition electrolyte formed above is placed in an electrolytic cell, two conductive electrodes with a thickness of 1 mm are taken, the distance between them is set to 0.5 cm, a bias voltage of 5 V is applied, and metal thermal conductive filler nanoparticles with a fractal growth morphology of metal copper and a sea urchin shape are obtained at the cathode.
[0040] (2) Preparation of sea urchin-shaped metal thermal conductive filler-thermal interface composite materials The organic silicon resin, curing agent and catalyst were mixed in a mass ratio of 98:1:1, and stirred at a speed of 500 rpm for 30 minutes to obtain a resin precursor. Then, the sea urchin-shaped metal nanoparticle thermal conductive filler prepared above was added, wherein the mass ratio of the thermal conductive filler to the organic silicon resin was 1:5, and stirred at a speed of 500 rpm for 30 minutes, and then applied into a 5.0 mm thick film, and cured at 100° C. for 20 minutes to obtain the high-toughness and high-thermal conductivity thermal interface composite material filled with the fractal growth sea urchin-shaped metal thermal conductive filler, such as Figure 3 shown.
[0041] Example 6 The method for preparing a high-toughness and high-thermal conductivity thermal interface composite material is basically the same as that in Example 5, except that in step (2), the mass ratio of the thermal conductive filler to the silicone resin is 1:10.
[0042] Example 7 The method for preparing a high-toughness and high-thermal conductivity thermal interface composite material is basically the same as that in Example 5, except that in step (2), the mass ratio of the thermal conductive filler to the silicone resin is 1:15.
[0043] Example 8 The method for preparing a high-toughness and high-thermal conductivity thermal interface composite material is basically the same as that in Example 5, except that in step (2), the mass ratio of the thermal conductive filler to the silicone resin is 1:20.
[0044] Table 1
[0045] Table 1 shows the thermal conductivity and mechanical properties of the thermal interface composite materials in Examples 4-8 of the present invention. The electrochemical workstation used for electrodeposition in the present invention is a Metrohm electrochemical workstation Autolab, and the thermal conductivity of the prepared thermal interface composite materials is obtained by using the Hotdisk hot plate method and testing in accordance with the international standard ISO 22007-2. The mechanical properties of the thermal interface composite materials are measured using a 3400 series universal tensile machine.
[0046] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-toughness and high-thermal-conductivity thermal interface composite material, characterized in that: The thermal interface composite material is composed of a matrix resin and a metal thermal conductive filler, wherein the matrix resin includes an organic silicon resin, a curing agent, a catalyst and a functional additive, and the thermal conductive filler is a fractal-grown metal nanoparticle; and the thermal conductivity of the thermal interface composite material is greater than 8.0 W / mK.
2. The high-toughness and high-thermal conductivity thermal interface composite material according to claim 1, characterized in that: The fractally grown metal nanoparticles have spherical and sea urchin shapes.
3. The high-toughness and high-thermal conductivity thermal interface composite material according to claim 1, characterized in that: The organic silicone resin is at least one of a linear vinyl silicone resin, a branched vinyl silicone resin, a modified silicone resin or a silicone gel, and the mass ratio of the organic silicone resin to the thermal conductive filler is 5 to 20:1; The curing agent is a combination of one or more of hydroxy silicone oil, vinyl silicone oil, hydrogen silicone oil or phenyl silicone oil, and the mass fraction of the curing agent in the base resin is 1% to 5%; The catalyst is at least one of a complex of chloroplatinic acid and isopropyl alcohol or divinyltetramethylsiloxane or diethyl phthalate, and the mass fraction of the catalyst in the matrix resin is 0.05% to 2%; The functional additive is one or more combinations of a thickener, an anti-aging agent, an anti-corrosion agent, and a flame retardant, and the mass fraction of the functional additive in the base resin is 0.1% to 5%.
4. The high-toughness and high-thermal conductivity thermal interface composite material according to claim 1, characterized in that: The metal thermal conductive filler is at least one of gold, silver, copper, aluminum, iron, zinc, and nickel nanoparticles.
5. A method for preparing a high-toughness and high-thermal conductivity thermal interface composite material, characterized in that: The steps include: Step 1, preparation of fractal growth metal thermal conductive filler; 1-1. Prepare electrolyte: metal nitrate as electrodeposition metal salt, ionic liquids of formula (Ⅰ-Ⅰ) and (Ⅰ-Ⅱ) as additives, and dimethyl sulfoxide as solvent; 1-2. Electrodeposition: Using ITO conductive glass as the cathode and anode, respectively, electroplating the electrolyte prepared in step 1-1 containing the ionic liquid additive of formula (Ⅰ-Ⅰ) or (Ⅰ-Ⅱ) in an electrolytic cell, electroplating to obtain spherical or sea urchin-shaped metal nanoparticles, respectively, washing and dispersing them in a tetrahydrofuran solution for standby use; Step 2, preparation of high-toughness and high-thermal conductivity thermal interface composite material; The silicone resin, curing agent and catalyst are mixed and stirred for 10 to 60 minutes to obtain a resin precursor, and then spherical or sea urchin-shaped metal nanoparticle thermal conductive filler is added and stirred for 10 to 60 minutes, and then it is applied into a 1 to 15 mm thick film, and cured at 50 to 140° C. for 5 to 60 minutes to obtain the high-toughness and high-thermal conductivity thermal interface composite material.
6. The method for preparing the high-toughness and high-thermal conductivity thermal interface composite material according to claim 5, characterized in that: The synthesis of the ionic liquid additives of formula (I-I) and (I-II) structures comprises the following specific steps: Add a solution A of chloromethyl ether in acetonitrile to a solution B of the intermediate product of formula II or III, react at 60-90° C. for 12-24 hours, and then post-treat to obtain an ionic liquid additive of formula (I-I) or (I-II); the ratio of the amount of the intermediate product of formula II or III to the amount of chloromethyl ether is 1:1.0-5.0; The method for preparing a high-toughness and high-thermal conductivity thermal interface composite material according to claim 5, characterized in that in the synthesis step of the structured ionic liquid additive described in formula (Ⅰ-Ⅰ) and (Ⅰ-Ⅱ), the volume amount of acetonitrile in the solution A is recorded as 10~20mL / g based on the mass of the intermediate product shown in formula Ⅱ or Ⅲ; The volume of acetonitrile in the solution B is recorded as 1-5 mL / g based on the mass of chloromethyl ether; The post-treatment method is: the reaction solution is decompressed to remove the solvent acetonitrile, the remaining mixture is fully washed three times with ether, the solvent is decompressed to remove the solvent and fully dried to obtain an ionic liquid additive with a structure shown in formula (I-I) or (I-II).
7. The method for preparing the high-toughness and high-thermal conductivity thermal interface composite material according to claim 5, characterized in that: The intermediate product represented by formula (II) is prepared as follows: at 25°C, morpholine and KOH are stirred in CH3CN for 3 h, and then 1-chloromethyl ether is added to the mixture, and the reaction is continued under reflux conditions for 48 h; the reaction mixture is subjected to rotary vacuum evaporation to remove the volatile solvent CH3CN, CH2Cl2 is added to the residue, extracted three times with water, and the organic phase is thoroughly dried with anhydrous Na2SO4; the collected organic phase filtrate is subjected to rotary vacuum evaporation to remove the solvent, and then thoroughly washed three times with ether, and the solid product obtained by removing the ether is finally dried in a dynamic vacuum oven at 45°C for 24 h to obtain the intermediate product represented by formula (II).
8. The method for preparing the high-toughness and high-thermal conductivity thermal interface composite material according to claim 5, characterized in that: The intermediate product represented by formula (III) is prepared as follows: pyrrolidine and KOH are stirred in CH3CN at 25°C for 3 h, and then 1-chloromethyl ether is added to the mixture, and the reaction is continued under reflux conditions for 48 h; the reaction mixture is subjected to rotary vacuum evaporation to remove the volatile solvent CH3CN, CH2Cl2 is added to the residue, extracted three times with water, and the organic phase is thoroughly dried with anhydrous Na2SO4; the collected organic phase filtrate is subjected to rotary vacuum evaporation to remove the solvent, and then thoroughly washed three times with ether, and the solid product obtained by removing the ether is finally dried in a dynamic vacuum oven at 45°C for 24 h to obtain the intermediate product represented by formula (III).
9. The method for preparing the high-toughness and high-thermal conductivity thermal interface composite material according to claim 5, characterized in that: In the electrodeposition step, the ITO conductive glass has a length of 5-50 cm, a width of 3-20 cm, a thickness of 0.5-5 mm, and a sheet resistance of 1-100 Ω / cm 2 ; The distance between the cathode and the anode is 0.02~1.0cm; The concentration of the ionic liquid additive in the electrolyte is 10~200mg / mL, the concentration of the metal nitrate is 50~150mg / mL, and the total amount of the electrolyte is 50~300mL; The electrodeposition voltage is 5~20V, and the current density is 10~100mA / cm 2 .
Citation Information
Patent Citations
Macromolecule thermal-conducting composite material and preparation method thereof
CN101921489A
Preparation method for three-dimensional composite Co<3>O<4>-Si-C negative electrode material
CN107068993A
Nanoparticle dispersions with ionic liquid-based stabilizers
US20110233458A1
Thermal interface materials using metal nanowire arrays and sacrificial templates
US20160251769A1
Thermal interface materials using metal nanowire arrays and sacrificial templates
WO2016137709A1
